Induction chemoradiotherapy versus chemotherapy alone for superior sulcus lung cancer. (August 2018) - Robinson, Lary A.; Tanvetyanon, Tawee; Grubbs, Deanna; Antonia, Scott; Creelan, Ben; Fontaine, Jacques; Toloza, Eric; Keenan, Robert; Dilling, Thomas; Stevens, Craig W.; Sommers, K. Eric; Vrionis, Frank
Highlights: Induction chemotherapy only may provide comparable outcomes to chemoradiotherapy. Impaired performance status patients may tolerate induction chemotherapy better. Induction therapy of some type offers improved results over initial surgery alone. Sublobar resection is an acceptable alternative when lobectomy is not feasible. Multimodality treatment involving experienced thoracic surgeons is advocated. Abstract: Objectives: Although treatment of superior sulcus tumors with induction chemoradiotherapy (CRT ) followed by surgery employed in the Intergroup INT-0160 trial is widely adopted as a standard of care, there may be significant associated morbidity and mortality. We describe our experience using standard and alternative induction regimens to assess survival rates and treatment toxicity in these patients. Materials and methods: Electronic medical records of all patients who underwent multimodality treatment including resection of lung cancer invading the superior pulmonary sulcus between 1994 and 2016 were retrospectively reviewed. Multivariable Cox Proportional Hazards model was constructed. Results: Of 102 consecutive patients, 53 (52%) underwent induction CRT, 34 (33%) underwent induction chemotherapy only (Ch ) followed by adjuvant radiotherapy, and 15 (15%) underwent no induction therapy followed by adjuvant therapy. There were 2 postoperative deaths (1.9%). To date, 42 patients are alive with a median follow-up 72.5 months. Overall 5-year survival rate was 45.4%. Survival was significantly influenced by age, FEV1, positive resection margins, surgical complications, but not the induction regimen. CRT resulted in higher complete pathological response rate than Ch : 38% vs. 3% ( p  < 0.001). CRT was associated with higher post-operative re-intubation rate: 13% vs. 0% ( p  = 0.03). Conclusions: Our single-institutional experience indicated that while induction CRT produced greater complete pathological response than Ch, it also increased the risk of post-operative complications. With careful patient selection, induction Ch followed by adjuvant radiotherapy may provide comparable survival outcomes to induction CRT . Since induction Ch is associated with lower risk of complications, it may be a particularly desirable choice for patients with impaired performance status.